A case of immunotherapy-induced thyroiditis - George Pears; Abhishek Mahajan; Anna Olsson-Brown; Joseph Sacco (Exploration of Targeted Anti-tumor Therapy, 2024)
Immunotherapy treatments for cancer are known to cause adverse thyroid events which present a diagnostic challenge to clinicians and radiologists. This case report highlights the importance of a high clinical index of suspicion and careful assessment of the thyroid on serial imaging studies to make the diagnosis. The case involves a 65-year-old male with malignant melanoma who was started on immunotherapy as part of a clinical trial. He developed thyroid dysfunction followed by an attack of acute neck pain. Ultrasound of his thyroid was performed which showed significant atrophy. A review of previous imaging was undertaken which confirmed the patient had suffered from thyroiditis and subsequent atrophy. Following this, the diagnosis of immunotherapy-induced thyroid dysfunction was made. Thyroxine supplementation and steroid dose were then adjusted causing his thyroid function and symptoms to improve. Immunotherapy agents for cancers are becoming more and more common. As the case report shows, physicians and radiologists will need to be vigilant to diagnose and treat any adverse events.